Checkers - Marsden, John, 1950- (New York : Dell Laurel-Leaf, 2000)
Speaking from a mental hospital, a teenage girl recounts the tremendous media pressure that preceded the breaking scandal of her father's unethical business dealings.
Previously published: Sydney : Pan Macmillan, 1996.
Book Links (A.L.A.).
Publisher's Weekly.
Wilson's Junior High School.
Young Adult
Keywords: Dogs -- Fiction; Family problems -- Fiction; Mental illness -- Fiction; Psychiatric hospitals -- Australia -- Fiction; Dogs -- Fiction; Family problems -- Fiction; Mental illness -- Australia -- Fiction; Psychiatric hospitals -- Australia -- Fiction; Australia -- Fiction; Australia -- Fiction